KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MEMBINA DISIPLIN MENGAJAR GURU SMA - Alfian Edi; Aliman Aliman; Manap Somantri (Manajer Pendididikan, 2017)
The general objective of this study is to describe the managerial skill of principal in fostering teacher’ teaching discipline in Senior High School 8 South Bengkulu. The research methods of this study was descriptive qualitative and the techniques of data collection were interview, observation and documentation. The research subjects were principal and teachers. The findings of this study show that the principal generally had applied several managerial skills in fostering teachers’ teaching discipline at Senior High School 8 South Bengkulu in accordance with the chacarteristic and the condition of the school.